Musical Facts and Sustainability of Trunthung Music in Eco-cultural Studies - Sinaga, Fajry Sub'haan Syah; Sinaga, Syahrul Syah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study aims to review the sustainability of Trunthung Music that shapes an ecosystem within the context of eco-culture. The study belongs to the nature of qualitative research with an interdisciplinary approach and several ecological concepts that reflect the culture of the peasant community over the slope of Merbabu Mountain in Magelang. The study itself is conducted in Warangan Hamlet and Gejayan Hamlet, the Regency of Magelang. The data are gathered through observation, documentation, and in-depth interviews with the informants related to the Trunthung Music. Then, the source triangulation technique is implemented through the test of trustworthiness by inspecting the data on the development of Trunthung Music toward the artists in Warangan Hamlet and the members of Lima Gunung Community. The data that have been attained from various sources are described, categorized, and eventually analyzed so that the ecosystem of Trunthung Music that has been on the progress can be identified. The results of the study show that Trunthung Music has been a performance that combines sonoric, kinesthetic, and visual dimensions, including their association with the natural condition and the peasant life over the Slope of Merbabu. The dialectics of Trunthung Music and the components of its ecosystem are in interaction with one another, resulting in the sustainability of the music until the present days. Then, the components of such ecosystem are the local agents who create the Trunthung Music and their interaction with the art community, be it with the Lima Gunung Community in the context of the Regency of Magelang and with the artists living outside the Regency of Magelang. In addition, the presence of Trunthung Music is associated with the traditional rites in the Warangan Hamlet, such as Nyadran Kali and Tapak Jaran Sembrani. All of these activities have good correlations among music, environment, and culture within the context of eco-culture.